Gender differences in information processing and transparency: cases of apparel brands' social responsibility claims. Issue 5 (17th August 2015) - Bhaduri, Gargi; Ha-Brookshire, Jung
Abstract : Purpose: – The purpose of this study was to understand how male and female consumers differently evaluate sustainability claims from brands and how brands' sustainability efforts and the presence/absence of information transparency in the claims affect their brand schemas differently. Design/methodology/approach: – Five hundred participants were recruited for an online experiment implementing both treatment and message variance. PROCESS, a recently developed regression-based bootstrapping technique was used to test the hypotheses. Findings: – Males were more likely than females to rely on their existing schemas for judgment in case of Made in USA but not Fair Labor claims. The presence of information transparency in claims reduced participants' reliance on their schemas. Practical implications: – The findings might be helpful for brands to design marketing claims with specific customer segments to stand out amidst advertisement clutter. Especially, brands targeting male consumers might try to build strong brand schemas starting the early stages of brand image building as males tend to consistently rely on their schemas for judgment. On the other hand, brands might benefit from providing transparent information about their sustainability efforts in their claims (especially those related to Made in USA) while targeting female consumers. However, irrespective of gender, brands might benefit from making claims with information transparency. Originality/value: – This study investigated the influence of gender in evaluation of brands' sustainability claims and the role of information transparency in the process, thereby filling a gap in literature. It is one of the very few studies to empirically investigate not only whether males and females are different in their information processing styles but also how such differences arise.